The Krakus’ and Wanda’s Burial Mounds of Cracow Krakova in Vandina gomila pri Krakovu - Leszek Paweł Słupecki (Studia Mythologica Slavica, 2015)
The author presents the Krakus and the Wanda’s burial mounds in the vicinity of Cracow, Poland. He has established that the connection between the figures of the Cracow legend and both mounds is more than just a product of 15th century literature, but originates from a much earlier tradition. Archaeological excavations of the Krakus’ mound indicated that the mound originates from the 9th and the 10th century. According to the author, the pagan peoples living along the Visla river created these mounds in the very center of their state as a response to the advancing Christianity from neighboring Moravia.